Hubungan Lama Bermain Pump It Up (PIU) Terhadap Nilai Indeks Massa Tubuh Pada Remaja - Rahmawan, Dito, Dwi Rosella Komalasari S.Fis., M.Fis., Dipl Cidesco (2016)
Along with the times, aerobic exercise can be done using the game Dance Interactive Video Games (IVDGs) provides many options for participating in physical activity one Pump It Up (PIU). Pumper (a term for a player in this game) are required to contract the muscles as much and as quickly as possible at an explosive rate and they must have a common endurance or aerobic capacity high enough to directly affect the percentage of body fat, if played in a specified period. Therefore, this study was conducted in order to determine the relationship of long-playing Pump It Up (PIU) to the value of body mass index in adolescents.